Integrating Gender across Research Programs - Meinzen-Dick, Ruth S. (2013)
"Partnering for Impact: IFPRI-European Research Collaboration for Improved Food and Nutrition Security" presentation by Ruth Meinzen-Dick, IFPRI, 25 November 2013 in Brussels, Belgium.